Relevansi Kualitas Layanan Terhadap Kepuasan Konsumen Pengguna Kereta Api Eksekutif - Widiyanto Widiyanto (STIE Widya Manggala, 2009)
Transportation service industries cannot be apart from competitive phenomenon. They, including the train service industry, must be able to compete to survive. This transportation competition, air-land-water, causes the decline of of executive class train passengers. This research would find out the service given by PT KAI to its customers in decision making to use transportation service. The data was primary data. The technique sampling was quota random sampling, which met data normally requirements. The result shows that there is an unfavorable relationship between image and quality of service represented by correlation coefficient 0,105. There is also an unfavourable relationship between employee’s performance and quality of service with correlation coefficient 0,113.